Good Corporate Governance sebagai Pemoderasi Pengaruh Financial Distress pada Opini Audit Going Concern - Wulandari, Ketut Memi; Muliartha, Ketut (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p15, 2019)
This research uses manufacturing companies listed on the Indonesia Stock Exchange as  research’s objects. The number of samples are 210 with using the purposive sampling  method. Data collection is done using documentation. The data analysis technique used is  Moderated Regression Analysis. Based on the results of the analysis, it was found that the  application of good corporate governance to the company is able to weaken the influence  of financial distress on the going concern audit opinion. The implications of the results of  the study support the signal theory seen in the results of the financial distress which tends  to signal the auditor to give a going-concern audit opinion. The results of the study also  support agency theory where the tendency for information asymmetry between agents and  principals, especially for companies in experience financial distress. Keywords: Financial distress, good corporate governance, going-concern audit opinion.